Foreign elite sport research system: design and key fields - Aranson, M. V.; Ozolin, E. S.; Shustin, B. N. (Theory and Practice of Physical Culture, 2018)
The study gives an analysis of the foreign elite sport research system, with a special analysis of the foreign theoretical and practical studies of the summer Olympic sport disciplines for the period of 2015-2017. The study gives a special attention to the study topics, their importance for the sport disciplines/ groups; their relevance for the sport insiders; contributions of the relevant agencies/ institutions/ centers including the health, education, research institutions, sport federations, clubs etc.; and the national compositions of the modern leading research teams.